2017
DOI: 10.1242/jcs.208546
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic loss of non-muscle myosin IIA and IIB is sufficient to induce mammary epithelial proliferation

Abstract: The mammary epithelium elaborates through hormonally regulated changes in proliferation, migration and differentiation. Non-muscle myosin II (NMII) functions at the interface between contractility, adhesion and signal transduction. It is therefore a plausible regulator of mammary morphogenesis. We tested the genetic requirement for NMIIA and NMIIB in mammary morphogenesis through deletion of the three NMII heavy chain-encoding genes (, and; also known as , and , respectively) that confer specificity to the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
8
7
0
Order By: Relevance
“…Based on these results, we suggest that P-MLC at the cell periphery prevents cell proliferation (Fig. 2D,G), consistent with a previous report that cell proliferation is induced by the mosaic loss of myosin and 50-75% of MLC 11 . The purpose of cell sheet culture is to connect cells to each other so that all the cells can be detached as an intact construct.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on these results, we suggest that P-MLC at the cell periphery prevents cell proliferation (Fig. 2D,G), consistent with a previous report that cell proliferation is induced by the mosaic loss of myosin and 50-75% of MLC 11 . The purpose of cell sheet culture is to connect cells to each other so that all the cells can be detached as an intact construct.…”
Section: Discussionsupporting
confidence: 92%
“…Based on these results, we suggest that P-MLC at the cell periphery prevents cell proliferation (Fig. 2 D,G), consistent with a previous report that cell proliferation is induced by the mosaic loss of myosin and 50–75% of MLC 11 .…”
Section: Discussionsupporting
confidence: 92%
“…Krt6a/Krt6b hemizygous null mice (Wong et al, 2000) are viable and were maintained in the inbred C57Bl/6 background (Rotty and Coulombe, 2012). K14-GFP-actin mice (Vaezi et al, 2002), Dsp fl/fl mice (Vasioukhin et al, 2001), and Myh9 fl/fl mice (Ma et al, 2009; Jacobelli et al, 2010; Nguyen-Ngoc et al, 2017) were gifts from A. Ewald (Johns Hopkins University, Baltimore, MD).…”
Section: Methodsmentioning
confidence: 99%
“…It also has angiogenesis, vascular remodeling abilities in vascular endothelial cells [66] and promotes tumor invasion, metastasis in some tumors [64,67]. Furthermore, Myh9 promotes tumor invasion and metastasis in some tumors [65,[68][69][70]. In addition, some studies have shown that Myh9 also contributes to cell proliferation, cell contraction, adhesion and cytokinesis.…”
Section: Discussionmentioning
confidence: 99%